Negative electrode material capable of regulating silicon dispersion and silicon-carbon gap and preparation method of negative electrode material
By using pore-making additives and dispersed nanosilicon or silicon agglomerates in the pores of amorphous carbon during the sintering process, the problem of cracking of the negative electrode material due to the expansion of silicon volume during charging and discharging is solved, and the high cycle stability and capacity maintenance of the material are achieved.
Patent Information
- Application Number
- CN202510157301.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-13
AI Technical Summary
During the charging and discharging process, existing negative electrode materials are prone to irreversible cracking due to the volume expansion of silicon, resulting in rapid attenuation of capacity.
By using pore-making additives during the sintering process, rich pores are left inside the carbon skeleton, and agglomerates of nano-silicon or silicon are dispersed in the amorphous carbon pores, and an adjustable gap exists between silicon and carbon to accommodate the volume expansion of silicon.
It effectively avoids cracking of the material during charging and discharging, provides a rich lithium ion transmission path, and improves the cycling stability and capacity retention ability of the material.
Smart Images

Figure CN119627088A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode material manufacturing, and in particular to a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are developing rapidly towards high energy density, in which the choice of negative electrode materials is crucial. Graphite, as the most mature commercial negative electrode material, can no longer meet higher requirements due to its low capacity. Therefore, silicon negative electrode materials have become a hot research object. Silicon, as a negative electrode material, has a high theoretical capacity, but during use, due to its severe volume expansion properties, there will be serious problems such as material capacity attenuation. Generally speaking, silicon is usually compounded with carbon materials in the form of silicon-carbon composite negative electrodes as negative electrode materials. The composite structure of silicon and carbon is very important. Silicon particles in nano form need to be evenly embedded in the carbon matrix, that is, the carbon layer forms a perfect wrapping of the silicon particles. Such a structure can enhance the conductivity between silicon and silicon, and at the same time provide a solid shell for the volume expansion of silicon.
[0003] This type of silicon and carbon composite can usually be achieved through surface coating technology. The coating technology is divided into solid, liquid and gaseous coating, solid coating.
[0004] Chinese patent application number CN201310282713.7 discloses a method for preparing porous Si / C composite microspheres, the process steps comprising: using a sodium alginate aqueous solution containing dispersed silicon as the aqueous phase and an isooctane solution containing an emulsifier as the oil phase, emulsifying the two uniformly under stirring, then adding a coagulant to crosslink and gel the sodium alginate droplets, then freeze-drying, and finally carbonizing under an inert atmosphere to obtain porous Si / C composite microspheres.
[0005] However, both the technical solution and the prior art still have the following problems: For example, the coating method is simple but the uniformity is poor by using the melt coating of asphalt above the softening point. Liquid coating is to dissolve other carbon sources such as resin, asphalt, sugar in a solvent, mix them with silicon for solid-liquid mixing, and form a uniformly coated silicon-carbon composite material after drying and carbonization. However, nanoscale silicon is prone to agglomeration in the carbon source solution, and the volume expansion of silicon during the charging and discharging process can easily cause irreversible cracking of the material, resulting in rapid capacity decay. Gaseous coating is to uniformly coat the gaseous carbon source on the silicon surface through a cracking-deposition process. The coating effect is good, but the process is complicated and expensive. In addition, the method of depositing nanosilicon into porous carbon through a gaseous silicon source, such as silane, can also achieve uniform distribution of silicon and carbon, but this process requires the use of silane gas with safety hazards, and has relatively high requirements for equipment and process. Summary of the invention
[0006] The purpose of the present invention is to address the deficiencies of the prior art. Through a special preparation method, during the sintering process, the pore-forming aid phase volatilizes, leaving abundant pores inside the carbon skeleton. The pores contain a large number of micropores and mesopores, which can provide abundant paths for the transmission of lithium ions, thereby solving the problem that when traditional negative electrode materials are made, the product is prone to irreversible cracking, resulting in rapid capacity decay.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap, comprising the following steps: Step 1: Disperse nano-silicon in a pore-forming agent, and add a certain amount of emulsifier to the pore-forming agent and mix them evenly, wherein the mass ratio of the emulsifier to the pore-forming agent is 1:4-1:10, and the mass ratio of nano-silicon in the pore-forming agent solution is 5%-40%; Step 2: preparing a resin oligomer solution by mixing phenol or phenol with an amine substance and an aldehyde substance at room temperature to prepare a clear and transparent resin solution; Step 3: Add the resin solution to the pore-forming agent solution and stir rapidly to form a non-transparent emulsion, wherein the mass ratio of the resin to the pore-forming agent in the resin solution is 1:0.5-1:2; the stirring rate is 500-4000 rpm / min, and the resin polymerization reaction is complete after stirring; Step 4: placing the reacted solution in an oven, and forming a block after the water evaporates, and heat-treating the block under an inert gas; Step 5: crushing and screening the heat-treated materials.
[0008] Preferably, the heat treatment temperature program is: S1, heating to temperature T1 at rate r1 and holding constant temperature for time t1, where r1 is 2~10℃ / min, T1 is 120~250℃, and holding constant temperature time t1 is 20~360min; S2, then raise the temperature to T2 at a rate of r2 and keep the temperature constant for t2, where r2 is 0.2~3℃ / min, T1 is 320~450℃, and the constant temperature time t1 is 60~180min; S3, finally heating to temperature T3 at rate r3 and keeping constant temperature for time t3, wherein r3 is 2-5℃ / min, T1 is 600-1000℃, and constant temperature time t1 is 60-300min; S4. Natural cooling.
[0009] Preferably, in step 1, the pore-forming aid component may be a long-chain alkane, including one of n-heptane, hexadecane, oleic acid, silicone oil, mineral oil, vegetable oil, or a combination of multiple thereof.
[0010] Preferably, in step 1, the emulsifier includes but is not limited to a combination of one or more substances selected from the group consisting of polyethylene glycol, cetyltrimethylammonium bromide, octylphenol polyoxyethylene ether, polyol fatty acid esters, polysorbate, sorbitan fatty acid esters, and stearyl alcohol polyether.
[0011] Preferably, the phenolic substance comprises one of phenol, cresol, m-cresol, o-cresol, catechol, resorcinol, hydroquinone, phloroglucinol, naphthol, and polycyclic phenol; The amine substance comprises one of melamine, dicyandiamide, aniline and benzoguanamine; Aldehyde substances include formaldehyde and furfural.
[0012] Preferably, in the step 1, the surface of the nano-silicon is pre-functionalized using a reagent selected from the group consisting of ammonia water and a silane coupling agent.
[0013] Preferably, the step three is carried out at a heating temperature ranging from 40 to 90°C.
[0014] Preferably, in the step three, a certain amount of catalyst is added, and the catalyst is one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, acetic acid solution, sodium hydroxide solution, sodium carbonate solution, potassium hydroxide solution, potassium carbonate solution, ammonia solution, and lithium hydroxide solution.
[0015] A negative electrode material comprises a combination of silicon and amorphous carbon, wherein silicon or silicon agglomerates are dispersed in pores inside the amorphous carbon, wherein the pore diameter of silicon is smaller than that of carbon pores, and silicon is bonded to the inner wall of the carbon pores.
[0016] Preferably, the particle size (D50) of the negative electrode material is 4-30 μm, and silicon is in the form of single nanoparticles with a particle size of 1-500 nm or nano silicon agglomerates with a particle size of 100-1000 nm.
[0017] The beneficial effects of the present invention are: (1) In the silicon-carbon composite material of the present invention, since the dispersion of silicon depends on the dispersion of the pore-forming agent phase, after the pore-forming agent volatilizes during the subsequent heat treatment, pores are left between silicon and carbon to accommodate the volume expansion of silicon, so that the material will not easily crack during charging and discharging in the battery, providing abundant paths for the transmission of lithium ions; (2) The present invention provides a buffer for the volume expansion of silicon during charge and discharge by adjusting the gap between nano-silicon or silicon agglomerates and carbon. The size of the gap can be adjusted by the silicon content in the pore-forming agent phase and the ratio of the resin phase to the pore-forming agent phase.
[0018] In summary, the present invention has the advantages of high product quality and relatively simple manufacturing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a morphology diagram of Example 3 of the present invention before coating; Figure 2 This is a morphology diagram of Comparative Example 1 of the present invention before coating; Figure 3 This is a schematic diagram of the present invention after carbonization at a low speed; Figure 4 It is a schematic diagram of the carbonization at high speed of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0022] Embodiment 1 like Figure 1-2 As shown, this embodiment provides a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap, including a combination of silicon and amorphous carbon, wherein silicon or silicon agglomerates are dispersed in pores inside the amorphous carbon, wherein the silicon pore size is smaller than the carbon pore, and silicon is bonded to the inner wall of the carbon pore; Furthermore, the particle size (D50) of the negative electrode material is 4-30 μm, and silicon is in the form of single nanoparticles with a particle size of 1-500 nm or nano silicon agglomerates with a particle size of 100-1000 nm.
[0023] The silicon-carbon composite material component in the present application is a combination of silicon and amorphous carbon, with a particle size (D50) of 4~30μm, wherein silicon can be a single nanoparticle with a particle size of 1~500nm, or a nanosilicon agglomerate with a particle size of 100~1000nm. Silicon or silicon agglomerates are dispersed in the pores inside the amorphous carbon. Silicon does not completely fill the pores in the carbon, but is slightly smaller than the pore size, that is, there is a gap between silicon and carbon.
[0024] It should be noted that in the silicon-carbon composite material of the present application, there is a certain gap between the nano-silicon or silicon agglomerates and the carbon, and the size of the gap is adjustable. The existence of these gaps can provide a buffer for the volume expansion of silicon during charging and discharging. The size of the gap can be adjusted by the silicon content in the pore-forming agent phase and the ratio of the resin phase to the pore-forming agent phase.
[0025] Embodiment 2 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse nano-silicon in a pore-forming agent, and add a certain amount of emulsifier to the pore-forming agent and mix them evenly, wherein the mass ratio of the emulsifier to the pore-forming agent is 1:4-1:10, and the mass ratio of nano-silicon in the pore-forming agent solution is 5%-40%; Step 2: preparing a resin oligomer solution by mixing phenol or amine and aldehyde substances at room temperature to prepare a clear and transparent resin solution; Step 3: Add the resin solution to the pore-forming agent solution and stir rapidly to form a non-transparent emulsion, wherein the mass ratio of the resin to the pore-forming agent in the resin solution is 1:0.5-1:2; the stirring rate is 500-4000 rpm / min, and the resin polymerization reaction is complete after stirring; Step 4: placing the reacted solution in an oven, and forming a block after the water evaporates, and heat-treating the block under an inert gas; Step 5: crushing and screening the heat-treated materials.
[0026] It is worth mentioning that nano silicon can be obtained by grinding micron silicon, and the particle size of micron silicon is 1~50μm.
[0027] Further, the heat treatment temperature program is: S1, heating to temperature T1 at rate r1 and holding constant temperature for time t1, where r1 is 2~10℃ / min, T1 is 120~250℃, and holding constant temperature time t1 is 20~360min; S2, then raise the temperature to T2 at a rate of r2 and keep the temperature constant for t2, where r2 is 0.2~3℃ / min, T1 is 320~450℃, and the constant temperature time t1 is 60~180min; S3, finally heating to temperature T3 at rate r3 and keeping constant temperature for time t3, wherein r3 is 2-5℃ / min, T1 is 600-1000℃, and constant temperature time t1 is 60-300min; S4. Natural cooling.
[0028] Furthermore, in step 1, the pore-forming aid component may be a long-chain alkane, including one of n-heptane, hexadecane, oleic acid, silicone oil, mineral oil, vegetable oil, or a combination of multiple substances thereof.
[0029] Furthermore, in step 1, the emulsifier includes but is not limited to a combination of one or more substances selected from the group consisting of polyethylene glycol, cetyltrimethylammonium bromide, octylphenol polyoxyethylene ether, polyol fatty acid esters, polysorbate, sorbitan fatty acid esters, and stearyl alcohol polyether.
[0030] Further, the phenolic substance comprises one of phenol, cresol, m-cresol, o-cresol, catechol, resorcinol, hydroquinone, phloroglucinol, naphthol, and polycyclic phenol; Aldehyde substances include formaldehyde and furfural.
[0031] Furthermore, in the step 1, the surface of the nano-silicon is pre-functionalized with ammonia water and a silane coupling agent, the purpose of which is to make the nano-silicon in the step 1 disperse faster in the pore-forming auxiliary agent phase.
[0032] Further, in the step three, the reaction is carried out at a heating temperature in the range of 40 to 90° C., the purpose of which is to accelerate the polymerization reaction. Alternatively, a certain amount of catalyst may be added in the step three, and the catalyst may be one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, acetic acid solution, sodium hydroxide solution, sodium carbonate solution, potassium hydroxide solution, potassium carbonate solution, ammonia solution, and lithium hydroxide solution.
[0033] Among them, in order to further optimize the surface of the material and reduce the specific surface area of the material as needed during the production process, the crushed material can be surface carbon-coated, and carbon coating refers to any one of gas phase coating, liquid phase coating, and solid phase coating.
[0034] In the present application, the key point is the adjustable dispersion technology of nano-silicon, in which nano-silicon is dispersed in a pore-forming agent phase, and the dispersion effect of silicon in carbon is achieved by dispersing the pore-forming agent phase in a carbon precursor, such as a resin phase. At the same time, the dispersion of silicon can be controlled. If a uniform dispersion of single nano-silicon particles is to be obtained, the pore-forming agent phase needs to be dispersed into nanoscale droplets in the resin. The control can be achieved by controlling the stirring rate. The faster the stirring rate, the more uniform the dispersion of the pore-forming agent phase and the more uniform the dispersion of nano-silicon. Similarly, if a uniform distribution of silicon clusters in porous carbon is to be obtained, the stirring rate can be appropriately slowed down to form larger droplets of the pore-forming agent phase.
[0035] Based on the above discussion, since the dispersion of silicon depends on the dispersion of the pore-forming agent phase, in the subsequent heat treatment process, after the pore-forming agent volatilizes, pores are left between silicon and carbon, which can accommodate the volume expansion of silicon and prevent the material from cracking easily during charging and discharging in the battery.
[0036] At the same time, the emulsion is used to promote the dispersion of nano-silicon in the porous carbon, and the dispersion degree of nano-silicon is changed by changing the dispersion of the pore-forming agent phase, and the dispersion of the pore-forming agent phase can be controlled by adjusting the shear rate during mixing. Therefore, the preparation method and structure control are simple.
[0037] Furthermore, due to the volatilization of the pore-forming additive phase during the sintering process, abundant pores are left inside the carbon skeleton. These pores contain a large number of micropores and mesopores, which can provide abundant pathways for the transmission of lithium ions.
[0038] Therefore, the size of silicon agglomerates in the silicon-carbon composite material in the present application, that is, the degree of dispersion of silicon in carbon, can be adjusted arbitrarily according to the dispersion of the resin phase and the pore-forming agent phase, and the adjustment method is to change the shear rate during mixing, change the polymerization rate of the resin, etc.
[0039] Embodiment 3 The morphology of the material Figure 1 As shown, a method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 60g of nano-silicon (D50=50nm) in a mixed pore-forming agent of 300g of oleic acid and 100g of cyclohexane, add 80g of polyethylene glycol thereto, and mix well; Step 2: Mix 300 g of phenol and 273 g of formaldehyde at room temperature and stir for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion, wherein the stirring rate is 1000 rpm / min, and continue stirring for 2 hours until the polymerization reaction is completed; Step 4: Place the reacted solution in an oven at 100°C, and after the water evaporates to dryness, form a block, and carbonize the block under nitrogen. The heating program is as follows: S1, heating at 5°C / min to 150°C and keeping the temperature constant for 120min; S2, then raise the temperature to 350°C at 1°C / min and keep the temperature constant for 120min; S3, finally raising the temperature to 700°C at 2°C / min and maintaining the temperature for 180min; S4. Natural cooling.
[0040] Step 5: crush the heat-treated carbonized material by ball milling and sieve it with a 200-mesh sieve.
[0041] It should be noted that the material is surface coated: take 100 grams of the crushed material, add 10 grams of coating asphalt, and coat it at 250°C using a melt coating machine. After coating, heat treat it at 1000°C for 2 hours in a nitrogen atmosphere to obtain a dry-coated material.
[0042] Embodiment 4 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 30g of nano-silicon (D50=50nm) in a mixed pore-forming agent of 400g of styrene and 100g of n-heptane, add 80g of polyethylene glycol thereto, and mix well; Step 2: Mix 195 g of phenol and 177 g of formaldehyde at room temperature and stir for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion, wherein the stirring rate is 1200 rpm / min. After stirring for 15 minutes, add 20 ml of 1M dilute hydrochloric acid and continue stirring for 2 hours until the polymerization reaction is complete; Step 4: Place the reacted solution in an oven at 80°C and wait for the water to evaporate to form a block. Carbonize the block under nitrogen with the following heating procedure: S1, heating at 5°C / min to 120°C and keeping the temperature constant for 60min; S2, then raise the temperature to 350°C at 1°C / min and keep the temperature constant for 120min; S3, finally raising the temperature to 800°C at 2°C / min, keeping the temperature constant for 120min, and then cooling naturally; S4. Natural cooling.
[0043] Step 5: crush the carbonized material by ball milling and sieve with a 200-mesh sieve.
[0044] It should be noted that the material was surface coated: 100 grams of the crushed material was taken, 30 grams of sucrose was added, and coated at 160°C using a melt coating machine. After coating, the material was heat treated at 850°C for 2 hours in a nitrogen atmosphere to obtain a dry-coated material.
[0045] Embodiment 5 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 50g of nano-silicon (D50=50nm) in a mixed solvent of 300g of oleic acid and 100g of cyclohexane as a pore-forming aid, add 100g of polysorbate thereto, and mix well; Step 2: Mix 344 g of o-cresol and 273 g of formaldehyde at room temperature and stir for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion, wherein the stirring rate is 2000 rpm / min. After stirring for 15 minutes, add 20 ml of 1M dilute hydrochloric acid and continue stirring for 2 hours until the polymerization reaction is complete; The heating procedure and other steps are the same as those in Example 4.
[0046] Embodiment 6 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 40g of nano-silicon (D50=80nm) in an ethanol solution, add 1.5ml of ammonia water, ultrasonicate for 1h, centrifuge to obtain nano-silicon powder treated with ammonia water, and then disperse the nano-silicon powder obtained by centrifugation in 250g of dimethyl silicone oil, stir for 30min, and then add 50g of polyvinyl alcohol to mix evenly; Step 2: Mix 187 g of phenol and 171 g of formaldehyde at room temperature and stir for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion at a stirring rate of 1000 rpm / min. After stirring for 20 minutes, add 20 ml of 3M dilute hydrochloric acid and continue stirring for 40 minutes until the polymerization reaction is complete; Step 4: Place the reacted solution in an oven at 100°C to form a block after the water evaporates. Carbonize the block under nitrogen at 700°C for 3 hours.
[0047] The heating procedure and other steps are the same as those in Example 3.
[0048] Embodiment 7 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 80g of nano-silicon (D50=110nm) in an ethanol solution, add 5ml of silane coupling agent, ultrasonicate for 1h, centrifuge to obtain nano-silicon powder treated with silane coupling agent, disperse the nano-silicon powder obtained by centrifugation in 150g of dimethyl silicone oil, stir for 30min to mix, then add 30g of sorbitol fatty acid ester and mix evenly; Step 2: Mix 187 g of phenol and 191 g of furfural at room temperature and stir for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion at a stirring rate of 1000 rpm / min. After stirring for 20 minutes, add 20 ml of 3M dilute hydrochloric acid and continue stirring for 40 minutes until the polymerization reaction is complete; Step 4: Place the reacted solution in an oven at 100°C, and after the water evaporates to dryness, form a block, and carbonize the block under nitrogen. The heating program is as follows: S1, heating at 8°C / min to 200°C and keeping the temperature constant for 90min; S2, then raise the temperature to 450°C at 0.5°C / min and keep the temperature constant for 90min; S3. Finally, the temperature was raised to 900°C at a rate of 2°C / min, and kept constant for 180min before being cooled naturally.
[0049] Step 5: crush the carbonized material by ball milling and sieve with a 200-mesh sieve.
[0050] It should be noted that the material was surface coated by taking 100 grams of the crushed material, adding 20 grams of coating asphalt, and coating it at 200°C using a melt coating machine: after coating, heat treatment was performed at 1000°C for 2 hours in a nitrogen atmosphere to obtain a dry-coated material.
[0051] Embodiment 8 The stirring rate in step 3 of Example 7 was changed to 1800 rpm / min.
[0052] The remaining steps are the same as those in Example 7.
[0053] Embodiment 9 The stirring rate in step 3 of Example 7 was changed to 3000 rpm / min. The remaining steps were the same as those in Example 7.
[0054] Embodiment 10 The stirring rate in step 3 of Example 7 was changed to 650 rpm / min. The remaining steps were the same as those in Example 7.
[0055] Embodiment 11 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Ultrasonic disperse 20g of nano-silicon (D50=120nm) in 400g of hexadecane, and then add 80g of octylphenol polyoxyethylene ether thereto and mix well; Step 2: 175 g of resorcinol and 306 g of furfural were prepared into an aqueous solution, mixed at room temperature, and stirred for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion at a stirring rate of 1800 rpm / min. Continue stirring for 2 hours until the polymerization reaction is complete. Step 4: Place the reacted solution in an oven at 100°C, and after the water evaporates to dryness, form a block, and carbonize the block under nitrogen at 700°C for 3 hours; The heating procedure and other steps are the same as those in Example 4.
[0056] It should be noted that the material was coated by taking 100 g of the crushed material, introducing acetylene and hydrogen into a CVD furnace, using argon as a carrier gas, and performing vapor phase coating at 800° C. for 4 hours to obtain a coated material.
[0057] Embodiment 12 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Ultrasonic disperse 40g of nano-silicon (D50=120nm) in 400g of coconut oil, then add 20g of sorbitan fatty acid ester and 50g of polysorbate and mix well.
[0058] Step 2: 175 g of resorcinol, 48 g of melamine and 272 g of formaldehyde were prepared into an aqueous solution, mixed at room temperature, and stirred for 20 min; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion at a stirring rate of 1600 rpm / min. Continue stirring for 2 hours until the polymerization reaction is complete. Step 4: Place the reacted solution in an oven at 100°C and wait for the water to evaporate to form a block. Carbonize the block under nitrogen at 900°C for 3 hours. The heating procedure and other steps are the same as those in Example 7.
[0059] It should be noted that the material is coated: 100 grams of the crushed material is added with 20 grams of sucrose, coated at 140°C using a melt coating machine, and after coating, heat treated at 700°C for 2 hours in a nitrogen atmosphere to obtain a dry-coated material.
[0060] Embodiment 13 The second step in Example 12 is changed to: 300 g of phenol, 64 g of dicyandiamide and 288 g of formaldehyde are prepared into an aqueous solution, mixed at room temperature, and stirred for 20 minutes. The remaining steps are the same as those in Example 12.
[0061] Embodiment 14 The second step in Example 12 is changed to: 270 g of phenol, 129 g of benzoguanamine and 260 g of formaldehyde are prepared into an aqueous solution, mixed at room temperature, and stirred for 20 minutes. The remaining steps are the same as those in Example 12.
[0062] Comparative Example 1 The morphology of the material Figure 2 As shown, a method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 60g of nano-silicon (D50=50nm) in 400g of ethanol; Step 2: 380 g of alcohol-soluble phenolic resin was dissolved in 400 g of ethanol to prepare a solution; Step 3: Add the solution in step 2 to the solution in step 1 and stir rapidly to form a non-transparent emulsion, wherein the stirring rate is 1000 rpm / min and the mixture is stirred rapidly for 1 hour to make the silicon evenly distributed in the resin; Step 4: Dry the mixture in an oven at 100°C to form a block, and carbonize the block under nitrogen at 700°C for 3 hours; The heating procedure and other steps are the same as those in Example 3.
[0063] The alcohol-soluble phenolic resin in this embodiment is in a gel state and is directly purchased from Hebei Zetian Chemical Co., Ltd.
[0064] Comparative Example 2 A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap comprises the following steps: Step 1: Disperse 60g of nano-silicon (D50=50nm) in a mixed pore-forming agent of 300g of oleic acid and 100g of cyclohexane and mix them evenly; The remaining steps are the same as those in Example 3.
[0065] The physical and chemical characteristic parameters of the silicon-carbon materials in the above embodiments and comparative examples are analyzed.
[0066] 1. Determination of silicon content of materials: obtained by thermogravimetric analysis.
[0067] 2. Specific surface area analysis of materials: test using nitrogen adsorption-desorption method.
[0068] 3. Material morphology observation: Observe by field emission scanning electron microscope.
[0069] The test results are shown in the following table:
[0070] Battery performance evaluation of materials: (1) preparing the obtained silicon-carbon material into a slurry, wherein the formula of the slurry is as follows: the silicon-carbon material, the binder, and the conductive agent are mixed in a ratio of 90:5:5 to prepare an aqueous dispersed slurry; wherein the binder is sodium carboxymethyl cellulose and styrene-butadiene rubber; and the conductive agent is conductive carbon black; (2) Coat the stirred slurry on the electrolytic copper foil, the wet film coating thickness is 300 μm, and dry it in vacuum at 80 degrees; (3) Assembling the prepared electrode into a button battery, wherein the counter electrode is a metal lithium sheet, the diaphragm is a polypropylene diaphragm, and the electrolyte is a 1M LiPF6 EC / DEC / EMC solution; (4) Perform constant current charge and discharge test with a voltage range of 0~1.5V and a current density of 0.1C.
[0071] The test results are as follows:
[0072] The sample morphology obtained in Example 3 is as follows Figure 1 As shown, there are pores of 1 micron or less in size inside the carbon, and nano-silicon is distributed in the pores. Since the ratio of silicon to pore-forming aid in Example 3 is relatively small, there is a large space around the silicon to accommodate the volume change of silicon during the charge and discharge process, and the material will not crack due to the expansion of silicon. As a control, in the sample of Comparative Example 1, silicon and carbon are tightly combined, and there is no space around silicon. Therefore, during the charge and discharge process, the volume expansion of silicon will cause the material to crack.
[0073] It can be seen from the battery performance test results that the silicon-carbon negative electrode material obtained by the preparation method provided by the present invention can make the raw silicon exert a good initial gram capacity. Among them, Examples 5 and 6 are not coated, and the specific surface area is large. This is because there are more micropores inside the carbon. Therefore, correspondingly, the first-week coulomb efficiency of Examples 5 and 6 is low, but the overall structural advantage makes it have good cycle stability. The remaining examples are all surface coated, so the first-week coulomb efficiency is also improved.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material capable of regulating silicon dispersion and silicon-carbon gap, characterized in that: The following steps are involved: Step 1: Disperse nano-silicon in a pore-forming agent, and add a certain amount of emulsifier to the pore-forming agent and mix them evenly, wherein the mass ratio of the emulsifier to the pore-forming agent is 1:4-1:10, and the mass ratio of nano-silicon in the pore-forming agent solution is 5%-40%; Step 2: preparing a resin oligomer solution by mixing phenol or phenol with an amine substance and an aldehyde substance at room temperature to prepare a clear and transparent resin solution; Step 3: Add the resin solution to the pore-forming agent solution and stir rapidly to form a non-transparent emulsion, wherein the mass ratio of the resin to the pore-forming agent in the resin solution is 1:0.5-1:2; the stirring rate is 500-4000 rpm / min, and the resin polymerization reaction is complete after stirring; Step 4: placing the reacted solution in an oven, and forming a block after the water evaporates, and heat-treating the block under an inert gas; Step 5: crushing and screening the heat-treated materials.
2. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: The heat treatment temperature program is: S1, heating to temperature T1 at rate r1 and holding constant temperature for time t1, where r1 is 2~10℃ / min, T1 is 120~250℃, and holding constant temperature time t1 is 20~360min; S2, then raise the temperature to T2 at a rate of r2 and keep the temperature constant for t2, where r2 is 0.2~3℃ / min, T1 is 320~450℃, and the constant temperature time t1 is 60~180min; S3, finally heating to temperature T3 at rate r3 and keeping constant temperature for time t3, wherein r3 is 2-5℃ / min, T1 is 600-1000℃, and constant temperature time t1 is 60-300min; S4. Natural cooling.
3. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: In the step 1, the pore-forming auxiliary agent component can be a long-chain alkane, including one of n-heptane, hexadecane, oleic acid, silicone oil, mineral oil, vegetable oil, or a combination of multiple substances thereof.
4. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: In the step 1, the emulsifier includes but is not limited to a combination of one or more substances selected from the group consisting of polyethylene glycol, cetyltrimethylammonium bromide, octylphenol polyoxyethylene ether, polyol fatty acid esters, polysorbate, sorbitan fatty acid esters, and stearyl alcohol polyether.
5. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: The phenolic substance comprises one of phenol, cresol, m-cresol, o-cresol, catechol, resorcinol, hydroquinone, phloroglucinol, naphthol and polycyclic phenol; The amine substance comprises one of melamine, dicyandiamide, aniline and benzoguanamine; Aldehyde substances include formaldehyde and furfural.
6. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: In the step 1, the surface of the nano-silicon is functionalized in advance using a reagent selected from ammonia water and a silane coupling agent.
7. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: In the step 3, the heating is carried out at a temperature ranging from 40 to 90°C.
8. The method for preparing a negative electrode material capable of adjusting silicon dispersion and silicon-carbon gap according to claim 1, characterized in that: In the step 3, a certain amount of catalyst is added, and the catalyst is one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, acetic acid solution, sodium hydroxide solution, sodium carbonate solution, potassium hydroxide solution, potassium carbonate solution, ammonia solution, and lithium hydroxide solution.
9. A negative electrode material, prepared based on the negative electrode material preparation method capable of adjusting silicon dispersion and silicon-carbon gap according to any one of claims 1 to 8, characterized in that: The invention comprises a combination of silicon and amorphous carbon, wherein silicon or silicon agglomerates are dispersed in the pores inside the amorphous carbon, wherein the pore diameter of silicon is smaller than that of the pores of carbon, and silicon is bonded to the inner wall of the pores of carbon.
10. A negative electrode material according to claim 9, characterized in that: The particle size (D50) of the negative electrode material is 4-30 μm, and silicon adopts one of nano single particles with a particle size of 1-500 nm or nano silicon agglomerates with a particle size of 100-1000 nm.
Citation Information
Patent Citations
A kind of preparation method of porous Si / C composite microsphere
CN104282894B
Preparation method and application of silicon carbon composite
CN108682813A
Silicon-based negative electrode material
CN112786848A
Preparation method for synthesizing silicon-carbon negative electrode material with double protective layers in one step and application of silicon-carbon negative electrode material
CN116314716A
Phenolic resin skeleton carbon layer coated nano silicon composite material and preparation method and application thereof
CN116914127A